Effect of Sorbitol and Chitosan Addition on Tensile Strength and Degradation Rate of Biodegradable Plastic from Rice Bran Starch - Zahra, Hayatun Nufus; Jonuarti, Riri; Gusnedi, Gusnedi; Hidayat, Rahmat (Universitas Negeri Padang, 2023)
The increasing use of plastic can cause enviromental pollution because plastic takes a very long time to decompose in the soil. Solutions that can be used to accelerate the process of plastic decomposition in the soil by replacing plastic making materials with natural polymer materials. Natural polymers are polymers produced from organic monomers, one of which is starch. Starch is one of the natural polymer materials used in the manufacture of biodegradable plastics, one of the natural materials containing starch is rice bran waste. From rice bran waste starch, bioderadable plastic can be made by adding chitosan and sorbitol by varying then succesively, namely 5:2:8, 5:3:7, 5:5:5, 5:7:3, 5:10:0, then making samples, then the samples are printed and tensile strength testing and degradation testing are carried out. From the tensile strength test results, the values obtained were 0.69 Mpa, 0.74 Mpa, 1.50 Mpa, 1.98 Mpa and 2.28 Mpa, respectively. The finel weight of the sampel after degradation is 0 gram, 0 gram, 0.0189 gram, 0.0226 gram, 0.1017 gram. It is concluded that biodegardable plastic with good tensile strength is in the variation of starch 5 grams, without sorbitol and chitosan 10 grams and for good degradation test in the variation of starch 5 grams, sorbitol 8 ml, chitosan 2 grams and variation of starch 5 grams, sorbitol 7 ml, chitosan 3 grams.